SISTEM INFORMASI APLIKASI PELAYANAN PANTI SOSIAL - Roida Pakpahan; Yuni Fitriani; Mahdiyyah Mahdiyyah (LPPM Nusa Mandiri, 2019)
Social institutions function to provide skills training to women who were previously commercial sex workers to have skills so they are able to find decent jobs or able to build independent businesses. At present the Harapan Mulia Social Institution has used an information system to manage the data of the assisted citizens but the use of its information system still has several disadvantages including; the program does not have a data search facility that has been fostered so that the search for data of the assisted citizens will take a long time, the certificate of the assisted citizens is not systemic so that the printed certificate will take a long time because the staff will manually retrieve the data again. This study aims to design information systems using software development using the waterfall method by adding data searches on applications and storing certificates in the system to speed up the work process of employees.